Rural Architecture: Case Study of Amirkola Village - Ghadi, Saed Farajnejad; Arzjani, Zahra; Saeed, Mirriahi; Azizpoor, Ali (International Journal of Bio-resource and Stress Management, 2010)
The diversity of environmental condition leads to the formation of different construction material and the techniques in usage of this materials cause to the formation of different housing types. Such diversity in the construction materials and housing types in appropriation with environment can be seen in Iran which has different climate areas and weather unstable conditions. Before the finding of new materials, the use of local material regarding to the capability with environment, availability, being economical and the most important reason, being the only present material resulting from environmental condition was common among the rural. Considering the fact that the major part of our population lives in the countryside and also the importance of domicile as one of the basic necessary of humor and the benefit of local material for rural and environment, study in this field is inevitable. The aim of this study is to identify local materials and house making techniques in Amirkola village by means of measurement methods based on visiting, observing and gathering information from the village to study housing types, benefits and shortcomings to present practical strategies for wise usage of the potentials.